PELUANG BISNIS ANGKRINGAN DI KOTA PALANGKA RAYA - Muhammad Riza Hafizi; Nita Oktaviana (AL-QARDH, 2017)
The people of Palangka Raya city in today's modern era made angkringan as a place of social interaction and place of consumption for all social layers of society. Therefore the authors seen the existence of business opportunities angkringan. Angkringan was a place to buy food and drink "typical". As for the formulation of the problem (1) How the sales strategy angkringan to achieve sales targets? (2) How was the business opportunity of angkringan in Palangka Raya city? (3) How was the feasibility of angkringan business in Palangka Raya city? This research method used descriptive qualitative approach. Data collection was done by used interview technique, observation, and documentation. The technique of determining the subject in this study used purposive sampling technique was the technique of determining the subject based on several considerations determined. Data validation was done by used triangulation. Further data the processed and analyzed with several stages: data collection, data presentation), conclusions (withdrawal by viewing data presentation), and Verification (drawing conclusions to answer from problem formulation). The results of this research were: (1) marketing strategy of angkringan business in Palangkaraya city to increased market share after passing strategic stages that was choosing strategic location, there wass no limited for all circle become its consumer, food menu provided safe for consumption, possible, clean place, affordable price and promotion through banner, social media and mouth of mouth; (2) angkringan business opportunities in the city of Palangka Raya had good prospects in the future and have the competence to do it, supported by the results of SWOT analyzed (strength, weaknesses, opportunities and threats); (3) feasibility study of angkringan business in Palangka Raya city, Jekan Raya Sub-district, the whole aspected was considered feasible. The market and marketing aspected of angkringan business was feasible to run because it has the market potential and the opportunity to market its products this was seen from the number of potential customers owned by the business. The social and cultural economic aspected can be said to be feasible because it had opened the job field, then from the aspected of business law angkringan was considered feasible because of the exemption from the Regulation of the Minister of Trade which states that not all businesses should be permits included the angkringan business.